Cultural ecology of heritage building adaptation in tropical cities. Issue 1 (May 2021) - Chang, B; Hasanah, A; Caesarina, H M
Abstract: The colonization left some buildings which still used by the cities until now. Rapid urbanization puts pressure on the sustainability of heritage buildings. Heritage buildings have not only historical-cultural values but also reflect the relationship between the building and its location or occupants. This article aims to identify the cultural ecology concept in the form of heritage building adaptation in tropical cities, as a part of heritage building conservation efforts. This research conducted a literature review method to specify the concept of cultural ecology and to find tropical cities' characteristics related to environmental aspects that affect the form of building adaptation. The results show that climate elements, topography, and vegetation conditions are important characteristics that affect the heritage building adaptation in tropical cities. The adaptation efforts that have been carried out on heritage buildings are the existence of additional elements in buildings that function to overcome the adverse effects environment conditions. The existence of heritage buildings for long periods is evidence that adaptation is an essential point in protecting and preserving heritage buildings. Building adaptation in the cultural ecology concept provides opportunities for heritage buildings to survive in a dynamic environmental condition and increasingly varied human needs.